Understanding Self-Esteem Holistically: Integrating Ontological, Epistemological, and Axiological Perspectives - Nur Kistin Kamalia; Wiryo Nuryono (International Journal Labs, 2026)
Self-esteem is one of the fundamental concepts in psychology that relates to an individual's assessment of his or her own worth. This article aims to examine self-esteem from a philosophical perspective that includes three main dimensions, namely ontology, epistemology, and axiology. The approach used is a literature study by examining various contemporary psychological and philosophical literature. Ontologically, self-esteem is understood as a psychological construct that is subjective but is formed through interaction between individuals and their socio-cultural environments. Epistemologically, knowledge of self-esteem is acquired through a variety of approaches, both empirical and reflective, which include psychometric measurements, behavioural observations, as well as the subjective experiences of individuals. Meanwhile, axiologically, self-esteem holds an important value in human life because it plays a role in the formation of self-identity, mental health, and the individual's ability to adapt and make decisions. The results of the study show that the understanding of self-esteem cannot be separated from the philosophical context behind it, so an integrative approach between psychology and philosophy is needed to understand this concept more comprehensively. Thus, the philosophical study of self-esteem makes an important contribution to the development of psychological theories and practices that are more reflective, contextual, and oriented towards human values.